PENGARUH SISTEM PENGENDALIAN INTERNAL, KETAATAN ATURAN AKUNTANSI, MORALITAS INDIVIDU DAN ASIMETRI INFORMASI TERHADAP KECURANGAN AKUNTANSI (Studi Empiris Pada OPD Kabupaten Rokan Hulu) - Trinisia, Karyn; Rasuli, M; Zarefar, Atika (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2025)
This study aims to analyze the effects of internal control systems, compliance with accountingrules, individual morality, and information asymmetry on accounting fraud. The researchwas conducted within the Regional Government Organizations (OPD) of Rokan HuluRegency. A quantitative approach was employed, with data collected through questionnairesdistributed to 129 respondents who are employees of OPDs under the Government of RokanHulu Regency. Data analysis was performed using the Partial Least Squares (PLS) methodwith the SmartPLS 4.0 software. The results show that all variables—internal control,compliance with accounting rules, individual morality, and information asymmetry—have asignificant effect on accounting fraud. These findings offer important implications for fraudprevention efforts through the enhancement of internal control systems, adherence toaccounting rules, strengthening individual morality, and reducing information asymmetry inpublic financial management.Keywords: accounting fraud, internal control, compliance with accounting rules, individualmorality, information asymmetry, OPD, PLS